Mapping human pressures on biodiversity across the planet uncovers anthropogenic threat complexes. Issue 2 (27th February 2020) - Bowler, Diana E.; Bjorkman, Anne D.; Dornelas, Maria; Myers‐Smith, Isla H.; Navarro, Laetitia M.; Niamir, Aidin; Supp, Sarah R.; Waldock, Conor; Winter, Marten; Vellend, Mark; Blowes, Shane A.; Böhning‐Gaese, Katrin; et al.
Abstract: Climate change and other anthropogenic drivers of biodiversity change are unequally distributed across the world. Overlap in the distributions of different drivers have important implications for biodiversity change attribution and the potential for interactive effects. However, the spatial relationships among different drivers and whether they differ between the terrestrial and marine realm has yet to be examined. We compiled global gridded datasets on climate change, land‐use, resource exploitation, pollution, alien species potential and human population density. We used multivariate statistics to examine the spatial relationships among the drivers and to characterize the typical combinations of drivers experienced by different regions of the world. We found stronger positive correlations among drivers in the terrestrial than in the marine realm, leading to areas with high intensities of multiple drivers on land. Climate change tended to be negatively correlated with other drivers in the terrestrial realm (e.g. in the tundra and boreal forest with high climate change but low human use and pollution), whereas the opposite was true in the marine realm (e.g. in the Indo‐Pacific with high climate change and high fishing). We show that different regions of the world can be defined by Anthropogenic Threat Complexes (ATCs), distinguished by different sets of drivers with varying intensities. We identify 11 ATCs that can be used to test hypotheses about patterns of biodiversity and ecosystem change, especially about the joint effects of multiple drivers. Our global analysis highlights the broad conservation priorities needed to mitigate the impacts of anthropogenic change, with different priorities emerging on land and in the ocean, and in different parts of the world. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstrakt: Der Klimawandel und andere anthropogene Faktoren, die die biologische Vielfalt verändern, betreffen nicht alle Teile der Erde in gleicher Weise. Während unsere Kenntnisse zu jedem einzelnen Gefährdungsfaktor ständig wachsen, ist unser Verständnis zu den räumlichen Beziehungen zwischen den verschiedenen Faktoren und ihr Zusammenwirken noch sehr mangelhaft. Das betrifft z.B. auch die Unterschiede zwischen terrestrischen und marinen Lebensräumen, die sehr unterschiedlichen Bedrohungen ausgesetzt sein können, selbst wenn sie eng benachbart sind. In der vorliegenden Studie haben wir globale Datensätze über Klimawandel, Landnutzung, Ressourcenausbeutung, Umweltverschmutzung, biologische Invasionen und Bevölkerungsdichte zusammengestellt. Mit Hilfe multivariater Statistiken haben wir die räumlichen Beziehungen zwischen diesen Ursachen des globalen Biodiversitätswandels und deren Kombinationen untersucht, um deren Einfluss auf verschiedene Regionen der Welt zu charakterisieren. Insbesondere in den terrestrischen Regionen wirken die genannten Gefährdungsfaktoren häufig in der gleichen Richtung, vor allem solche, die zum Teil besonders hohe Belastungen darstellen. Regionen mit stärker ausgeprägtem Klimawandel sind tendenziell solche Gebiete, in denen die Gefährdung durch andere Faktoren eher geringer ist, wie z.B. in der Tundra und im borealen Nadelwald, die stark vom Klimawandel, aber weniger von hoher Nutzungsintensität und Verschmutzung betroffen sind. Dagegen treten in den Meeresregionen gegenteilige Muster auf, wo z.B. im Indopazifik ein sehr ausgeprägter Klimawandel einer hoher Ressourcenausbeutung durch Fischerei zusammenfällt. Die Regionen der Welt lassen sich in Klassen unterschiedlicher Interaktionen und Intensitäten dieser anthropogenen Gefährungsfaktoren unterteilen. Diese insgesamt 11 verschiedene Faktorenklassen können nun dazu verwendet werden, Auswirkungen auf Biodiversität zu untersuchen und die Gefährdungs‐Hotspots zu identifizieren. Diese Hotspots sind diejenigen großräumigen Meeres‐ und Festlandsregionen, in denen prioritär Naturschutzmaßnahmen angewendet werden müssen, um den Auswirkungen des anthropogenen Biodiversitätswandels entgegenzutreten. A free Plain Language Summary can be found within the Supporting Information of this article.